High-Precision baseflow separation in data-scarce regions with machine learning models - Rong Zhong; Hang Lyu; Xiaosi Su; Tingting Deng; Aimin Cai; Yanxi Wu; Jingzun Mao; Peng Zhou (Journal of Hydrology, 2026)

Contamination characteristics and airflow regulated transport of microbial aerosols in a hospital respiratory ward - Lina Hu; Zhijian Liu; Guangpeng Yao; Zikai Shang; Chenxing Hu; Lianhe Lu; Rui Rong; Tong Zhou; Duo Cai (Journal of Hazardous Materials, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Apportioning nitrate sources via dual isotope, PMF and SIAR in a complex urban river network during flood season: Implications for engineered mitigation strategies - Xin Wang; Qiaoyun Lin; Zhixiong Huang; Yihua Cai; Wenjing Wang; Nan Rong; Siye Wei; Renren Wu; Quan Zhou (Journal of Water Process Engineering, 2026)

Superenhancer-driven SMC4 promotes myeloma growth by epigenetically enhancing IFI16-dependent STING signaling - Jiayun Guan; Xuanyi Lin; Zhenfeng Dai; Jianbiao Zhou; Zhen Cai; Tze King Tan; Tae-Hoon Chung; Xiaochen Zhang; Wee-Joo Chng; Xiaoxiang Rong; Yunlu Jia (Apoptosis, 2026)

Aquaporin-1 stabilizes β-catenin to promote NLRP3 inflammasome-mediated pyroptosis in rheumatoid arthritis - Meng-yuan Zhou; Zi-yao Gao; Jing Sun; Wen-cai Long; Juan Zhou; Wen-jing Fang; Xue-chun Wang; Sheng-dong Wu; Rong Li (Apoptosis, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Microbial electrotrophs-driven molecular transformations of dissolved organic matter in paddy soil - Rong Tang; Xiaoshan Luo; Wenjie He; Xixi Cai; Lingyan Huang; Lihua Zhou; Yong Yuan (Journal of Environmental Management, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

QTL Mapping and Candidate Gene Analysis for Wax Trait of Stem and Leaf in Durum Wheat (Triticum turgidum L. ssp. durum (Desf.)) - Yijing Cai; Yasir Muhammad; Yujie Zhou; Yuefen Cao; Junkang Rong; Xin Hu (Plant Molecular Biology Reporter, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Nanomedicine constructed with plant-derived aromatic aldehydes treats low back pain by reversing the progression of lumbar facet joint osteoarthritis - Ming Yang; Hui Lv; Zhenzhen Tang; Jiangling Zhou; Qiandong Yang; Juan Cai; Yingtao Gui; Bo Yu; Rong Huang; Jing Yang; Ying Bao; Dinglin Zhang; et al. (Chemical Engineering Journal, 2025)

First report of Colletotrichum siamense causing anthracnose on Evodia rutaecarpa in Hunan, China - Mengshan Sun; Jin Xie; Liu Cai; Rong Song; Li Zhou (Journal of Plant Pathology, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Volatile organic compounds in typical coal chemical industrial park in China and their environmental and health impacts - Jieting Zhou; Min Gao; Hongmei Xu; Ruiqing Cai; Rong Feng; Kun He; Jian Sun; Steven Sai Hang Ho; Zhenxing Shen (Atmospheric Environment, 2024)

Evolution of phosphate metabolism in Tibetan wild barley to adapt to aluminum stress - Shengguan Cai; Yuqing Huang; Yang Liu; Liyuan Wu; Dezhi Wu; Rong Liu; Peter R. Ryan; Meixue Zhou; Guoping Zhang; Zhong-Hua Chen (Plant and Soil, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

Numerical study on thermal–hydraulic behaviors of a natural circulation system with petal-shaped fuel rod bundle - Jian-Chuang Sun; Rong-Jiang Zhou; Xiang-Fei Meng; Jin-Yi Cao; Wen-Chao Zhang; Jin-Cheng Wang; Wei-Hua Cai (Annals of Nuclear Energy, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Nitrogen removal performance and mechanism in constructed wetlands under saline conditions: Role of Canna indica inoculated with Piriformospora indica - Naxin Cui; Min Cai; Xu Zhang; Rong Zeng; Li Zhou; Guifa Chen; Guoyan Zou (Bioresource Technology, 2024)

A deep learning network for improving predictions of maximum and minimum temperatures over complex terrain - Lin Xu; Li Zhou; He Chen; Rong-Hui Cai; Yue Zhou (Theoretical and Applied Climatology, 2024)

The environmental analysis and site selection of mussel and large yellow croaker aquaculture areas based on high resolution remote sensing - Lina Cai; Jie Yin; Xiaojun Yan; Yongdong Zhou; Rong Tang; Menghan Yu (Acta Oceanologica Sinica, 2024)

Recognizing topological attributes and spatiotemporal patterns in spotted seals (Phoca largha) trophic networks based on eDNA metabarcoding - Yan Xu; Fei Huang; Mingliang Zhou; Rui Gu; Jie Zhu; Qiangqiang Rong; Yanpeng Cai (Frontiers in Marine Science, 2023)
Spotted seals, a protected species, face multifaceted threats to their habitat, which in turn impact the closely associated trophic networks. These threats will lead to irreversible structural variations within the ecosystem. Therefore, investigating the topological variability of trophic networks in spotted seals is important. Applying environmental DNA methods, field sample collection was conducted in 2021 during both the sea fishing moratorium period and the fishing period to decode fish diversity. Assessing the current status of fish resources by using the multivariate statistics approach. Applying dietary information establishes the spotted seals’ trophic network. Selecting 12 network indexes to analyze the spatiotemporal patterns of network topological attributes. As a result, about 51 families, and 76 genera species were identified. During the sea fishing moratorium and the fishing period, there are 12 and 18 different food resources available for spotted seals, respectively. The diversity index revealed that the FP had greater species richness and diversity than the SP. Comparatively, the Fishing period exhibited higher species richness and biodiversity, likely influenced by habitat heterogeneity and anthropogenic activities. Additionally, the topological features of networks reflected the high clustering coefficients (CC=0.35) and the proportion of omnivorous species (O≈60%), indicating that the network structure in this region tends to form higher trophic-level clustering patterns, which facilitate the formation of weaker interactions between clusters, enhancing the robustness of the network. The higher connectivity complexity index during the fishing period (SC=12.3) supported that the spotted seal’s trophic network was relatively more stable in this period. Thus, during the fishing period, it is crucial to pay more attention to the intensity of human fishing on mid-to-high trophic-level omnivorous fish resources to ensure the sustainability of these potential food resources for spotted seals. This comprehensive study achieved three key objectives: (a) utilizing eDNA to characterize fish diversity during distinct periods, (b) establishing trophic networks of spotted seals, and (c) discerning topological attributes and spatiotemporal patterns within the ecological network. Overall, this study can provide technical and data support for integrated ecological network management and propose suggestions for protecting and recovering spotted seals.

Injectable, tough and adhesive zwitterionic hydrogels for 3D-printed wearable strain sensors - Jiating Liu; Yueyun Zhou; Jiawei Lu; Rong Cai; Tian Zhao; Ying Chen; Mengxue Zhang; Xiang Lu; Yi Chen (Chemical Engineering Journal, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Emergence of the clinical rdar morphotype carbapenem-resistant and hypervirulent Klebsiella pneumoniae with enhanced adaption to hospital environment - Congcong Liu; Ning Dong; Xueting Huang; Zixian Huang; Chang Cai; Jiayue Lu; Hongwei Zhou; Jingren Zhang; Yu Zeng; Fan Yang; Gongxiang Chen; Zhangqi Shen; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

Carbon dots as light-responsive oxidase-like nanozyme for colorimetric detection of total antioxidant capacity in fruits - Jinquan Li; Yun Zhou; Yue Xiao; Shuo Cai; Changsheng Huang; Shuo Guo; Yuanqiang Sun; Rong-Bin Song; Zhaohui Li (Food Chemistry, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

A self-supported sodium alginate composite hydrogel membrane and its performance in filtering heavy metal ions - Rong Cai; Ying Chen; Jiawei Hu; Jinli Xiong; Jiawei Lu; Jiating Liu; Xiaobo Tan; Wenyong Liu; Yueyun Zhou; Yi Chen (Carbohydrate Polymers, 2023)

The spatial-temporal consistency of chlorophyll-a and fishery resources in the water of the Zhoushan archipelago revealed by high resolution remote sensing - Lina Cai; Rong Tang; Xiaojun Yan; Yongdong Zhou; Jingjing Jiang; Menghan Yu (Frontiers in Marine Science, 2022)
Details of the chlorophyll- a (Chl- a ) distribution in the water of the Zhoushan archipelago were analyzed based on data from the panchromatic multispectral sensor (PMS) of the GaoFen-6 (GF-6). A new Chl- a inversion model was built using in-situ Chl- a and the green-red bands of the 2 m spatial resolution GF-6/PMS image. Combined with fishery data, the relationship between Chl- a concentration and fish resources were revealed. The results show that: (1) High Chl- a concentration area was mainly concentrated in the nearshore intensive islands waters, and Chl- a concentration changes obviously with the change of tidal currents. Chl- a concentration around islands increases, especially downstream of islands. Seasonally, Chl- a concentration is higher in spring and summer, lower in autumn, and lowest in winter. (2) The change of fish eggs and larvae in the water of the Zhoushan archipelago shows consistency with the spatial distribution and seasonal variation of Chl- a . (3) The interaction between tidal currents and islands results in the diverse currents (upstream upwelling and downstream vortex currents) around the islands, promoting vertical water exchange and the uplifting of nutrients, resulting in a high overall Chl- a concentration in the waters around the islands. The diverse flow conditions, the ideal nutrient-rich environment, and the abundant phytoplankton attract a large number of fish to gather and breed in the waters around the islands. (4) Chl- a of intensive island waters is an essential indicator for fish spawning grounds.

Identifying Supercooled Liquid Water in Cloud Based on Airborne Observations: Correlation of Cloud Particle Number Concentration with Icing Probability and Proportion of Spherical Particles - Yuquan Zhou; Can Song; Miao Cai; Siyao Liu; Yang Gao; Rong Zhang (Journal of Meteorological Research, 2022)

Effect of biochar on transformation of dissolved organic matter and DTPA-extractable Cu and Cd during sediment composting - Meihua Zhao; Caiyuan Cai; Zhen Yu; Hongwei Rong; Chaosheng Zhang; Shungui Zhou (Environmental Science and Pollution Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Converting rice husk to biochar reduces bamboo soil N2O emissions under different forms and rates of nitrogen additions - Rong Zhou; Ali El-Naggar; Yongfu Li; Yanjiang Cai; Scott X. Chang (Environmental Science and Pollution Research, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Textural and map contrasts of the subduction-collision boundary between the Philippine Arc and the Sunda margin - Zhou-rong Cai; Jun-yang Xiang; Qiang-tai Huang; Zheng-xin Yin; Yong-jian Yao; Hai-ling Liu; Bin Xia (Arabian Journal of Geosciences, 2016)

Geochronology, geochemistry, and Sr–Nd–Pb isotopes of Cretaceous granitoids from western Tibet: petrogenesis and tectonic implications for the evolution of the Bangong Meso-Tethys - Qiang-Tai Huang; Zhou-Rong Cai; Bin Xia; Jian-Feng Li; Lian-Ze Xia; Hui-Chuan Liu (International Geology Review, 2016)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Age and composition of the Rebang Co and Julu ophiolites, central Tibet: implications for the evolution of the Bangong Meso-Tethys - Wei-Liang Liu; Bin Xia; Yun Zhong; Jian-Xin Cai; Jian-Feng Li; Hong-Fei Liu; Zhou-Rong Cai; Zhi-Lei Sun (International Geology Review, 2014)

Author’s Reply to Discussion of the Paper “An Empirical Failure Criterion for Intact Rocks” by Peng et al. (2013) - Jun Peng; Ming Cai; Guan Rong; Chuangbing Zhou; Xiaojiang Wang (Rock Mechanics and Rock Engineering, 2014)

An Empirical Failure Criterion for Intact Rocks - Jun Peng; Guan Rong; Ming Cai; Xiaojiang Wang; Chuangbing Zhou (Rock Mechanics and Rock Engineering, 2014)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Isolation and characterization of an AP2/ERF-RAV transcription factor BnaRAV-1-HY15 in Brassica napus L. HuYou15 - Jing Zhuang; Chao-Cai Sun; Xi-Rong Zhou; Ai-Sheng Xiong; Jian Zhang (Molecular Biology Reports, 2011)

Discovery and expression profile analysis of AP2/ERF family genes from Triticum aestivum - Jing Zhuang; Jian-Min Chen; Quan-Hong Yao; Fei Xiong; Chao-Cai Sun; Xi-Rong Zhou; Jian Zhang; Ai-Sheng Xiong (Molecular Biology Reports, 2011)

Detection of plasmid-mediated IMP-1 metallo-β-lactamase and quinolone resistance determinants in an ertapenem-resistant Enterobacter cloacae isolate - Li-rong Chen; Hong-wei Zhou; Jia-chang Cai; Rong Zhang; Gong-xiang Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

Evaluation of Aegilops tauschii Cosson for preharvest sprouting tolerance - Liu Deng-Cai; Lan Xiu-Jin; Wang Zhi-Rong; Zheng You-Liang; Zhou Yong-Hong; Yang Jun-Liang; Yen Chi (Genetic Resources and Crop Evolution, 1998)